2018
DOI: 10.1159/000492393
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation Potential-Related Protein Promotes the Esophageal Cancer Cell Proliferation, Migration and Suppresses Apoptosis by Mediating the Expression of p53 and Interleukin-17

Abstract: Objective: This study aims to investigate the mechanism of proliferation potential-related protein (PP-RP) in influencing the proliferation, migration, and apoptosis of esophageal cancer cells. Methods: Quantitative real-time PCR and western blotting were performed to analyze the expression of PP-RP gene, p53, and interleukin (IL)-17 in human normal tissues and tumor tissues, as well as the expression of p53 and IL-17 in Eca109 and TE3 cells. The esophageal cancer cell proliferation was detected by 3-(4,5-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the present study, it was found that DIM, a natural phytochemical Through KEGG analysis, it was found that DIM may be involved in the apoptosis, IL-17 and PI3K-Akt signaling pathways. A study has shown that TP53 and IL-17 can affect the proliferation and migration of esophageal cancer cells (22). Furthermore, PI3K-Akt can affect the proliferation, invasion and metastasis of a variety of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was found that DIM, a natural phytochemical Through KEGG analysis, it was found that DIM may be involved in the apoptosis, IL-17 and PI3K-Akt signaling pathways. A study has shown that TP53 and IL-17 can affect the proliferation and migration of esophageal cancer cells (22). Furthermore, PI3K-Akt can affect the proliferation, invasion and metastasis of a variety of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations in levels may be explained by the overexpression of the protein, the mislocalization of unassembled or misassembled protein [37]. Various studies have corroborated that SNRPG may contribute signi cantly to the initiation and progression of cancers [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SNRPG in different cancers can be explained by high levels of protein, the mis-localization of unassembled or misassembled proteins [29] . Thus, SNRPG might contribute to the initiation and progression of different cancers [30][31][32][33][34] . We found that SNRPE was highly expressed in tumor tissues by using ONCOMINE [16] , but the results of SNRPF and SNRPG groups were not similar in this study.…”
Section: Discussionmentioning
confidence: 99%